2013
DOI: 10.1007/978-3-642-40480-1_32
|View full text |Cite
|
Sign up to set email alerts
|

Here or There? How Configuration of Transnational Teams Impacts Social Capital

Abstract: Abstract. The many challenges of distributed communication and the many challenges of intercultural collaboration have been researched and discussed at length in the literature. What is lacking is a combined approach that looks at both issues of distance and diversity in collaboration. We conducted research in a large, multinational technology company to better understand team configurational factors in transnational work. In this case study, we found that the development of social capital is impacted by wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Close proximity, in-person work provides opportunities for unplanned interactions in-office that would build trust. Interactions in remote settings must now be intentional or it will affect social capital across distributed teams [14]. In remote settings, there is a need for more devoted time, resources, communication channels, and events to foster relationships.…”
Section: Working Remotelymentioning
confidence: 99%
“…Close proximity, in-person work provides opportunities for unplanned interactions in-office that would build trust. Interactions in remote settings must now be intentional or it will affect social capital across distributed teams [14]. In remote settings, there is a need for more devoted time, resources, communication channels, and events to foster relationships.…”
Section: Working Remotelymentioning
confidence: 99%
“…Global organizations can choose to configure and structure their teams in a wide variety of ways. Haines et al (2013) found important to understand the implications of various transnational team configurations. The authors conducted a research in a large multinational technology company and they found that the development of social capital is impacted by whether a person is in their home context or transplanted and their expectations based on that context.…”
Section: Supporting Human Collaborative Work and Cognitive Strategiesmentioning
confidence: 99%